Hubungan Tingkat Partipisasi Keluarga Pada Pelaksanaan Program Gammara’na dalam Menurunkan Angka Kejadian Stunting Di Wilayah Kerja Puskesmas Kota Kabupaten Enrekang - Resky Devi Akib; Nur Laela; Nasrayanti Nurdin (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2022)
Stunting is one of the problems that occur in toddlers today. Globally, stunting in children under five years old reached 165 million in 2011. According to the World Health Organization (WHO) in the Global Nutrition Targets 2025, stunting is an irreversible growth disorder that is influenced by mostly inadequate nutritional intake and is caused by repeated infections for 1000 days. first life. Therefore, it is very important for children aged 0-2 years to ensure optimal nutritional intake. This study aims to determine the relationship between the level of family participation in the Gammara'na program in reducing the incidence of stunting in the work area of ​​the Enrekang City Health Center. The work of the Enrekang Regency City Health Center. This study used survey methods of analytic correlation with a cross sectional approach.  with atotal sampling using sampling, data analysis using Chi Square. There was an association level of the family participation on the Implementation of the Gammara'na Program in Reducing Stunting Incidents with a P value =0.026 < 0.05.